The Impact of Lifestyle on Proper Thyroid Gland Function - Kanarszczuk, Julia; Kawa, Zuzanna; Kasprzak, Maria; Jędrzejewska, Aleksandra; Jureczko, Aleksandra; Kleczaj, Klaudia; Starczewski, Łukasz; Jaworowska, Julia; Babiarz, Gabriela; Osiński, Damian (Quality in Sport, 2026)
Introduction. Lifestyle significantly influences the functioning of the thyroid gland, especially in the case of hypothyroidism. Regular physical activity, a proper diet, an adequate amount of sleep and stress reduction can contribute to improving hormonal test results and alleviating the symptoms of this condition. Recent studies also highlight the role of vitamin D and gut microbiota. Their proper levels and the balance of microorganisms in the gut may support the immune system and influence hormonal regulation. A balanced diet rich in essential micronutrients, such as iodine, selenium, and zinc is an important element supporting therapy. This paper provides an overview of current scientific reports on the impact of selected lifestyle factors on the course of hypothyroidism. Available research results suggest that modifying daily habits can be a significant supplement to therapy, positively affecting the functioning of the thyroid gland and the quality of life of patients. Research objective. The objective of this review is to summarize the current scientific evidence concerning the impact of selected lifestyle factors on thyroid gland function. Conclusions. Based on the analysis of the available literature, it can be concluded that lifestyle plays a significant role during hypothyroidism and in maintaining the proper functioning of the thyroid gland. A well-balanced diet, regular physical activity and effective reduction of chronic stress may support therapy, positively influence hormonal balance and contribute to the alleviation of disease symptoms. Furthermore, an increasing number of studies highlight the importance of maintaining adequate vitamin D levels and gut microbiota balance in the regulation of thyroid function and support of the immune system. Therefore, the modification of daily habits constitutes an important adjunct to the treatment of hypothyroidism and may contribute to improving patients’ quality of life.